2023
DOI: 10.1021/acs.jafc.3c03715
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Analysis of Veterinary Drugs in Food Samples by Developing a High-Resolution Tandem Mass Spectral Library

Adeeba Khadim,
Syed Usama Yaseen Jeelani,
Muhammad Noman Khan
et al.

Abstract: Veterinary drug residues present in foods can pose severe health threats to the population. The present study aims to develop a high-resolution mass spectral library of 158 veterinary drugs of 16 different classes for their rapid identification in food samples through liquid chromatography−high-resolution electrospray ionization-tandem mass spectrometry (LC-HR-ESI-MS/MS). Standard drugs were pooled according to their log P values and exact masses before analysis. Spectra were collected at system automated coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…The major advantages of the workflow are (1) it uses the feature abundance in SG normalized mice urine for improved quantification to select suspect metabolite candidates, (2) it combines two complementary chromatographies, and positive and negative ionization modes to cover the polar metabolites in urine produced via phase I and II metabolism (e.g., sulfation, glucuronidation), (3) it can be applied to any chemical and is not limited to the phase I and II metabolites. In addition to traditional spectral libraries constructed using chemical standards, , considerable progress has recently been made in constructing metabolite MS2 libraries of chemicals of concern using human liver S9 incubations for nontargeted screening. , Such approaches are performed on a compound-by-compound basis and include dedicated sample preparation (e.g., extraction and glucuronidase treatment) and yield curated libraries with structure annotation based on MS2 fragmentation patterns. With the same goal to improve nontargeted suspect screening, we pursued the creation of more comprehensive, suspect metabolite MS2 libraries resulting from mammalian whole body metabolism (vs S9 preparations).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major advantages of the workflow are (1) it uses the feature abundance in SG normalized mice urine for improved quantification to select suspect metabolite candidates, (2) it combines two complementary chromatographies, and positive and negative ionization modes to cover the polar metabolites in urine produced via phase I and II metabolism (e.g., sulfation, glucuronidation), (3) it can be applied to any chemical and is not limited to the phase I and II metabolites. In addition to traditional spectral libraries constructed using chemical standards, , considerable progress has recently been made in constructing metabolite MS2 libraries of chemicals of concern using human liver S9 incubations for nontargeted screening. , Such approaches are performed on a compound-by-compound basis and include dedicated sample preparation (e.g., extraction and glucuronidase treatment) and yield curated libraries with structure annotation based on MS2 fragmentation patterns. With the same goal to improve nontargeted suspect screening, we pursued the creation of more comprehensive, suspect metabolite MS2 libraries resulting from mammalian whole body metabolism (vs S9 preparations).…”
Section: Resultsmentioning
confidence: 99%
“…Despite extensive research on fungicides, a number of reported metabolites are not in chemical databases such PubChem (e.g., tebuconazole–COOH (Figure C), tebuconazole glucuronides and sulfates), which impedes their detection in nontargeted data sets. Furthermore, even libraries constructed using chemical standards, as for example veterinary drugs, are not readily available despite linking to public repositories. We have deposited the mice urinary data sets in the MetaboLights repository and made the MS2 spectral libraries available in MoNA .…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, a variety of analytical methods have been used to evaluate Lin in different real samples including GC-MS (Tao et al, 2011), LC-MS (Khadim et al, 2023), LC-MS/MS (Fernandes-Cunha et al, 2015;Maddaleno et al, 2019;Du et al, 2021;Li et al, 2021), and immunoassay (Zhou et al, 2014;Cao et al, 2015). Although these methods have many advantages, especially good sensitivity and accuracy, most of them suffer from several drawbacks, such as costly instruments, complicated sample preparation, long time consumption, and poor storage stability.…”
Section: Introductionmentioning
confidence: 99%